2013
DOI: 10.1016/s1995-7645(13)60030-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between IL-1β, IL-1Ra gene polymorphism and occurrence of polycystic ovary syndrome infertility

Abstract: T allele of the 511 site of IL-1β gene and V allele of the second introne of IL-1Ra gene might be the genetic basis of the rising of IL-1β, IL-1Ra and US-CRP levels in blood serum of PCOS patients, and are associated with the infertility occurrence of PCOS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…Eight publications were excluded for insufficient or uncorrelated data according to our inclusion criteria [9,11,10,14,13,23,24,30]. Finally, 18 articles met the inclusion criteria and were selected [8,7,27,12,28,18,15,17,20,19,22,21,25,26,29,31,16]. The study selection process is shown in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight publications were excluded for insufficient or uncorrelated data according to our inclusion criteria [9,11,10,14,13,23,24,30]. Finally, 18 articles met the inclusion criteria and were selected [8,7,27,12,28,18,15,17,20,19,22,21,25,26,29,31,16]. The study selection process is shown in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…For IL-1A -889C>T (rs1800587), 310 cases and 279 controls from 2 studies [25,20] were analyzed. For IL-1B -511C>T (rs16944), we looked at 482 cases and 421 controls from 4 studies [25,8,18,16]. For the IL-1B +3953C>T polymorphism (rs1143634) in exon 5, 223 cases and 188 controls from 2 studies were included [18,25].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In the present study, we hypothesized that increasing systemic levels of IL‐1Ra may affect insulin secretion by β‐cells and also reflect increased subclinical inflammatory activity associated with impaired glucose metabolism in women with PCOS. Moreover, the impact of body mass index (BMI) on systemic IL‐1Ra levels was also investigated, as there have been conflicting results as regards its role …”
Section: Introductionmentioning
confidence: 99%
“…Recently, cytokines have emerged as key contributors to human reproductive activities, and participate in the modulation of ovarian functions [14]. Xia et al found that IL-1β was increased in serum, and positively correlated with the incidence of PCOS [15]. Gallinelli et al reported that IL-12 was decreased in the follicular fluid of PCOS patients compared to controls, and the increased IL-13 was associated with the occurrence and development of PCOS [16].…”
Section: Introductionmentioning
confidence: 99%